CSR, risk management quality and corporate sustainable performance: A mediated moderation of corporate performance and environmental uncertainty - Rosa Fitriana; Wahyudin Zarkasyih; Harry Suharman; Citra Sukmadilaga (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
This study explores the complex interactions that exist between corporate social responsibility (CSR), risk management quality, corporate sustainable performance (CSP), and the moderating role of environmental uncertainty. Grounded in resource-based view theory, a cross-sectional field survey was conducted based on a sample of 291 managers working in Indonesian state-owned enterprises (SOEs). The data set was analyzed through partial least square based structural equation modeling using SmartPLS software. The results show that CSR and risk management quality have a significant impact on CSP. Moreover, results revealed that corporate performance (CP) significantly mediates these relations. Environmental uncertainty was found a significant moderator between CP and CSP. The study adds to the corporate sustainability literature by clarifying the complex relationships between CSR, risk management, and sustainable performance in the context of Indonesian SOEs.
Keywords: 330; State-owned enterprises; corporate social responsibility; corporate sustainableperformance; risk management quality; environmental uncertainty; Indonesia